Design of high performance, low power sub thresholds ram using source coupled logic for implantable applications. - Vasudeva Reddy, T; B.K. Madhavi, Dr (International Journal of Engineering and Technology, 2018)
Low power circuits functioning in sub threshold were proposed in earlier seventies. Recently, growing with the need of low power consumption, the low power circuits have became more attractive. However, the act of sub threshold design logics has become sensitive to the supply voltage & process variations like temperature and so on. In sub threshold region of operations the supply voltage (Vgs) is less than the threshold (Vth).This leads to less power dissipation in over all circuit, but drastically increment in propagation delay. The major intention of the paper is to offer new low power & less delay digital circuits. SRAM is the major power drawing element and dissipation is about 40% in total power. The primary objective is to design of sub threshold SRAM design, Functionality and performance is estimated from the power and delay.The second objective is to offer novel Source coupled logic based SRAM (ST-SC SRA) M & Operating these design under sub threshold operating region. Performance is analyzed through power and delay. Finally comparing the traditional sub threshold SRAM with source coupled based SRAM in power and delay on par with the performance. Discussing some of the applications, where there is a requirement of less power and delay.Â